2019
DOI: 10.1155/2019/3619864
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Surgery Might Be a Better Option for Subcapsular Thyroid Microcarcinomas

Abstract: For high-risk papillary thyroid microcarcinomas (PTMCs), immediate surgery is recommended. This study aimed to evaluate the location of PTMCs in the thyroid lobe and determine whether location is associated with an aggressive biology and the necessity of immediate surgery. This retrospective study included 288 patients who underwent initial surgery for PTMC. Clinical data were extracted. Subcapsular thyroid microcarcinomas (STMs) and nonsubcapsular thyroid microcarcinomas (NSTMs), distinguished by ultrasound, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…(2) Multifocality, subcapsular nodule, trachea, and recurrent laryngeal nerve invasion are considered as predictors of poor prognosis of PTC [145][146][147][148][149]. Thus, when category 4A nodules are multiple, or immediately adjacent to the trachea or recurrent laryngeal nerve, ultrasound-guided FNA can be considered if the nodule is >10 mm; (3) For solitary nodule of ≤10 mm that is not immediately adjacent to the capsule, trachea or recurrent laryngeal nerve, regular follow-up is optional; (4) If the nodules are too large to cause compression symptoms or cosmetic problems, the management principle of TIRADS 2-3 nodules can be referred to, provided the biopsy results are benign.…”
Section: Management Recommendationsmentioning
confidence: 99%
“…(2) Multifocality, subcapsular nodule, trachea, and recurrent laryngeal nerve invasion are considered as predictors of poor prognosis of PTC [145][146][147][148][149]. Thus, when category 4A nodules are multiple, or immediately adjacent to the trachea or recurrent laryngeal nerve, ultrasound-guided FNA can be considered if the nodule is >10 mm; (3) For solitary nodule of ≤10 mm that is not immediately adjacent to the capsule, trachea or recurrent laryngeal nerve, regular follow-up is optional; (4) If the nodules are too large to cause compression symptoms or cosmetic problems, the management principle of TIRADS 2-3 nodules can be referred to, provided the biopsy results are benign.…”
Section: Management Recommendationsmentioning
confidence: 99%
“…Micropapillary thyroid carcinoma has a less aggressive behavior and mostly presence without any symptoms [3]. Recent studies have shown more than 400% increase in micropapillary thyroid carcinoma prevalence along with the improvement of imaging technologies [33].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some authors classified there were low-risk and high risk disease. Thus, immediate surgical management was being reconsidered and debated [3]. Active surveillance has emerged to address the concern for over-treatment of low-risk papillary microcarcinoma [4].…”
Section: Introductionmentioning
confidence: 99%
“…According to K-TIRADS, decision-making concerning the FNA of subcentimeter high-suspicion nodules depends upon the management strategy of the thyroid microcarcinomas and FNA is recommended in patients with poor prognostic factors, including suspected cervical LN metastases, obvious ETE to adjacent structures, confirmed distant metastases, or suspected medullary thyroid cancer [23]. However, subcapsular location of tumor also known to have been associated with aggressive behavior of papillary thyroid microcarcinoma, and it may be on the same spectrum of disease progression with ETE as a more frequent subcapsular location may more often progress to ETE [27][28][29][30]. Our results are compatible with those studies in terms of different therapeutic strategies being required when dealing with aggressive variants of PTC that tend to show more ETE-favoring preoperative US findings.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%